Tanggung Jawab China Sebagai Negara Pihak Dalam Maritime Labour Convention 2006 Atas Tindakan Nahkoda Kapal Penangkap Ikan Berbendera China - Gozal, Kenxie; Wisnu Aryo Dewanto; Muhammad Insan Tarigan (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Indonesian Shipmen died on a Chinese ship. According to their information, while working on the ship, they received improper treatment such as working beyond reasonable time, eating and drinking that did not meet their needs. In addition they must also continue to work even in sick conditions by receiving improper wages. This article aims to analyze the state of China responsible for the actions of the captain and / or the ship company that did not carry out obligations in the 2006 maritime labor convention which was ratified by China since November 12, 2015. This study uses a normative juridical method, namely by conducting a library study of legal ingredients. The results of this study are that China as a State Party in the 2006 Maritime Labor Convention must carry out the obligations agreed at the convention based on the Pacta Sun Servanda principle. Failure to implement the 2006 Maritime Labor Convention which results in losses for the state or other citizens may lead to the responsibility of the Chinese state as a party to the convention. Ship companies are also responsible for deviating from the provisions in the 2006 Maritime Labor Convention in the form of improper treatment such as working beyond reasonable time, eating and drinking that is not in accordance with their needs. In addition they must also continue to work even in sick conditions by receiving improper wages.